Informal freelancers in the time of COVID-19: Insights from a digital matching platform in Mozambique - Sam Jones; Ivan Manhique (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
Despite the severe negative economic shock associated with the COVID-19 pandemic, evidence from many contexts points to a surge in sales on online platforms, as well as shifts in the composition of demand. This paper investigates how the pandemic has affected both the supply of and demand for informal manual freelancers in Mozambique. Using data from the digital labour marketplace Biscate, we quantify dynamics along four main dimensions: responses to infection rates, official restrictions on activity, changes in workplace mobility, and employment conditions. Overall, we find both positive and negative effects of the pandemic on growth in the supply of workers, which add up to a zero net effect on average. However, on the demand side, the contact rate and task agreement rate increased by around 50 per cent versus the 'no shock' counterfactual. These findings underline how the informal sector plays a valuable shock-absorbing role and that digital labour marketplaces can facilitate adjustments to economic shocks.
Keywords: J23; J46; O17; 330; freelancers; COVID-19; economics shocks; Mozambique; informal sector